Pengaruh Media Sosial dan Teman Sebaya terhadap Perilaku Remaja dalam Budaya Clubbing pada Generasi Z di Kota Semarang - Ayuningtiyas, Erlinda Putri; Sari, Woro Apriliana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to examine the analysis of the influence of social media and peers on adolescent behavior in clubbing culture in generation Z in Semarang City. The population in this study were all generation Z in Semarang City who follow clubbing culture. The number of samples in this study was 100 generation Z in Semarang City who follow clubbing culture. The sampling technique used the purposive sampling method. The research method used is quantitative with data sources in the form of primary data. The data analysis method used multiple linear regression analysis with SPSS version 22. The results of this study provide evidence that partially and simultaneously the variables of social media and peers have a positive effect on adolescent behavior